Dynamically triggered seismicity in Japan following the 2024 M w 7.5 Noto earthquake - Like An; Bogdan Enescu; Zhigang Peng; Masatoshi Miyazawa; Hector Gonzalez-Huizar; Yoshihiro Ito (Earth, Planets and Space)
Abstract On January 1st, 2024, a moment magnitude (M w ) 7.5 earthquake occurred on an active reverse fault in the northern part of Noto Peninsula, being one of the largest intraplate events recorded in Japan. In previous studies, the dynamic triggering of seismicity in Japan following some large remote earthquakes has been well documented, such as in the case of the 2011 M w 9.0 Tohoku–Oki earthquake, the 2016 M w 7.1 Kumamoto earthquake, and other large teleseismic events. In this study, we investigate the remote triggering of microearthquakes by the 2024 Noto earthquake and their characteristics. We analyze waveform data recorded at high-sensitivity seismic stations in Japan, before and after the occurrence of the Noto mainshock. Local earthquakes are detected on high-pass filtered three-component seismograms. Low-pass filtered waveforms are used for visualizing the mainshock surface waves and estimating dynamic stresses. Our results show a relatively widespread activation of small earthquakes—none of them listed in the Japan Meteorological Agency (JMA) earthquake catalog—that were triggered by the passage of the mainshock surface waves in many regions of Japan. These include Hokkaido and Tohoku in northeastern Japan, Kanto in central Japan, and Kyushu in southern Japan. The triggering is mostly observed in volcanic regions, supporting the hypothesis that such places are relatively easy to be activated dynamically, likely due to the excitation of fluids by the passage of mainshock surface waves. The calculated dynamic stress changes estimated from peak ground velocities, which triggered the earthquakes after the Noto mainshock, are in the range 12.8–102.6 kPa. We also report potential, less well-constrained dynamic triggering by the Mw 5.3 Noto foreshock, which occurred ~ 4 min before the mainshock, at levels of stress about 100 times smaller. The analysis of a longer-term (1 month) seismicity pattern, based on the JMA catalog, revealed a statistically significant increase of seismicity in the remote Akita–Yakeyama (Tohoku region) volcanic area, following the Noto earthquake. Graphical Abstract